Comic Adventures of Boots - Kitamura, Satoshi (New York : Farrar Strausgiroux, 2002)
A collection of comic strips featuring the adventures of a mischievous cat named Boots.
K-3.
Keywords: Cartoons and comics -- Fiction; Cats -- Fiction